PHOTOSYSTEM II INHIBITOR HERBICIDES - PART I - SILVA, ILCA P. DE F. E; JUNIOR, JOSUÉ F. DA S.; PUTTI, FERNANDO F.; LATORRE, DEBORA DE O.; SCHIMIDT, ANA P.; LUDWIG, RAFAEL (Revista Brasileira de Engenharia de Biossistemas, 2013)
Chemical control has been the most used in large planting areas, especially for being a fast and efficient method. Herbicides inhibitors of photosystem II (PSII) are critical for integrated weed management and soil conservation practices. The application is carried out pre-emergence or early post-emergence of weeds. The absorption by the roots is, with the barrier splines Caspari is made ​​by translocation xylem. The process of absorption and translocation are also dependent on the characteristics of the product as lipophilic and hydrophilic properties which can be measured by the octanol-water partition coefficient (Kow). The inhibition occurs by connection of the herbicides of this group QB binding site in the D1 protein of photosystem II, which is located at the thylakoid membrane of the chloroplast, causing the blocking transport of electrons from QA to QB, interrupting CO2 fixation and production of ATP and NAPH2.